Coding coenzyme handles: a hypothesis for the origin of the genetic code. - Szathmáry, E (1993)
The coding coenzyme handle hypothesis suggests that useful coding preceded translation. Early adapters, the ancestors of present-day anticodons, were charged with amino acids acting as coenzymes of ribozymes in a metabolically complex RNA world. The ancestral aminoacyl-adapter synthetases could have been similar to present-day self-splicing tRNA introns. A codon-anticodon-discriminator base complex embedded in these synthetases could have played an important role in amino acid recognition. Extension of the genetic code proceeded through the take-over of nonsense codons by novel amino acids, related to already coded ones either through precursor-product relationship or physicochemical similarity. The hypothesis is open for experimental tests.